2020
DOI: 10.1215/00127094-2019-0069
|View full text |Cite
|
Sign up to set email alerts
|

A McKay correspondence for reflection groups

Abstract: We construct a noncommutative desingularization of the discriminant of a finite reflection group G as a quotient of the skew group ring A = S * G. If G is generated by order two reflections, then this quotient identifies with the endomorphism ring of the reflection arrangement A(G) viewed as a module over the coordinate ring S G /(∆) of the discriminant of G. This yields, in particular, a correspondence between the nontrivial irreducible representations of G to certain maximal Cohen-Macaulay modules over the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…We are interested in complex reflection groups, since in [16] the first three authors established a McKay correspondence for true reflection groups, i.e., groups generated by complex reflections of order 2: the nontrivial irreducible representations of such a group G were shown to correspond to maximal Cohen-Macaulay modules over the discriminant of the reflection group, in particular, they correspond to the isotypical components of the hyperplane arrangement, viewed as a module over the coordinate ring of the discriminant, see [16,Thm. 4.17].…”
Section: ) Let ([α] δ) and ([β] δ ) Be Two Vertices Of (G) Then There Is An Arrow With Source ([α] δ) And Target ([β] δ ) Whenever [β]mentioning
confidence: 99%
See 2 more Smart Citations
“…We are interested in complex reflection groups, since in [16] the first three authors established a McKay correspondence for true reflection groups, i.e., groups generated by complex reflections of order 2: the nontrivial irreducible representations of such a group G were shown to correspond to maximal Cohen-Macaulay modules over the discriminant of the reflection group, in particular, they correspond to the isotypical components of the hyperplane arrangement, viewed as a module over the coordinate ring of the discriminant, see [16,Thm. 4.17].…”
Section: ) Let ([α] δ) and ([β] δ ) Be Two Vertices Of (G) Then There Is An Arrow With Source ([α] δ) And Target ([β] δ ) Whenever [β]mentioning
confidence: 99%
“…Finally a comment on how this paper came into being: In the first preprint version on the arXiv of [16] we had already determined the McKay quivers of G(1, 1, n), and Section 3 of the current paper appeared originally there. However, it made sense to combine it with the results of M. Lewis' thesis about the McKay quivers of the general G(r, p, n) [36], that now make up Sections 4 and 5 of the current paper.…”
Section: ) Let ([α] δ) and ([β] δ ) Be Two Vertices Of (G) Then There Is An Arrow With Source ([α] δ) And Target ([β] δ ) Whenever [β]mentioning
confidence: 99%
See 1 more Smart Citation
“…Theorem 1.1 is an extension of [BFI20] where, for a complex reflection group generated by reflections of order 2, it is shown that End R/∆ S/(z) is a NCR for R/(∆). The groups G(2k, k, 2) are generated by order 2 reflections.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we give a short introduction to discriminants of finite reflection groups and our construction of their noncommutative desingularizations. The details of our new results will be published elsewhere [BFI16].…”
Section: Introductionmentioning
confidence: 99%